Rhynchosia ganesanii, a new name for Rhynchosia fischeri P. Satyanar. & Thoth. (Leguminosae: Papilionoideae), from India - Kottaimuthu, Ramalingam; Vasudevan, Natarajan (Phytotaxa, 2015)
A new name Rhynchosia ganesanii is proposed to replace Rhynchosia fischeri P. Satyanar. & Thoth., which is an illegitimate later homonym of R. fischeri Harms.